A Pragmatic Approach for Detecting nCOVID-19 using Pervasive Computing Based on Dual Diagnostic Measures - Biswas, Swarnava; Chakraborty, Chandranath; Chawla, Riddhi; Paul, Dabosmita; Sen, Debajit; Sarkar, Niloy; Mukherjee, Moumita (International Journal of Statistics in Medical Research, 2021)
Our regular way of life has been disrupted by the COVID-19, and we have been obliged to accept the procedures that are in place under the new normal regime. It is envisaged that the standard diagnostic technique will evolve throughout the course of the procedure. As a help to this type of diagnostic technique, our research group is developing a tool. In this article, the group discusses the importance of employing two diagnostic metrics that have proven to be pivotal in many diagnoses for doctors, and how they might be used to their advantage. Together, natural language processing-based symptoms measures and a machine learning-based strategy that takes into account medical vitals can help to minimise the error percentage of detection by as much as 50%. The technique suggested in this study is the first of its type, and the authors have obtained findings that are satisfactory in terms of accuracy. A further justification for suggesting such a strategy is the manner in which a fusion algorithm might arrive at the correct results from two concurrent algorithms performing the same task. One of the group's other objectives was to give the doctor a valuable opinion in the form of such an architectural design. The suggested design may be employed at any point of care facility without the need for any additional infrastructure or escalation of the current amenities to accommodate the proposed architecture.